PENGARUH KOMUNIKASI, INFORMASI, DAN EDUKASI (KIE) MELALUI MEDIA LEAFLET DAN VIDEO TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG PAPARAN PORNOGRAFI DI SMP NEGERI 1 SIDAMANIK KEC. SIDAMANIK KAB. SIMALUNGUN TAHUN 2016 - Rotua Lenawati Tindaon (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2018)
ABSTRACTThe development of communication and information technology has positive and negative impacts. It negative impact is the exposure to pornographic content. Continuous pornographic exposure will influence adolescents’ sexual behavior, damage their brain, and most probably become pornographic addicts all their life. Therefore, it is necessary to increase their knowledge and attitude toward pornographic exposure through health counseling. The objective of the research was to find out the influence of KIE (communication, information, and education) through leaflet and video media on adolescents’ knowledge and attitude toward pornographic exposure. The research used quasi experiment method. The population was all Grades VII and VIII students of SMP Negeri I, Sidamanik, and 60 of them were used as the samples which consisted of 30 respondents in the leaflet group and the other 30 respondents in the video group.The result of the analysis showed that there was the influence of counseling with leaflet media about pornographic exposure on students’ knowledge (p=0.000) and attitude (p=0.000). There was the influence of counseling with video media about pornographic exposure on students’ knowledge (p=0.0000 and attitude (p=0.000).Video media was more effective in increasing knowledge (p=0.000) and attitude than leaflet media in counseling about pornographic exposure. It is recommended that the students be more proactive in participate in counseling about pornography which has the influence on reproductive health and use leaflet and video as the media in order to increase their behavior in forestalling pornographic exposure. Keywords: Leaflet, Video, Knowledge, Attitude, Pornographic Exposure.